To find: f o g, g o f ,(f o g) (2) and (g o f) (-3)
Formula used: (i) f o g = f(g(x))
(ii) g o f = g(f(x))
Given: (i) f : R → R : f(x) = x2 + 2
f o g = f(g(x))
Ans) = 6
g o f = g(f(x))
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation